BETTER OFF ALONE: DAILY SOLITUDE IS ASSOCIATED WITH LOWER NEGATIVE AFFECT IN MORE CONFLICTUAL SOCIAL NETWORKS. (11th November 2018) - Birditt, K; Manalel, J; Sommers, H; Luong, G; Fingerman, K L
Abstract: Older adults are often considered at risk for social isolation. Little is known, however, about how often older adults lack social contact (in person, phone, electronic) throughout the day, the implications of lacking contact (i.e., solitude), and whether the effects of solitude vary by the broader social context. Participants were from the Daily Experiences and Well-being Study (DEWS) which included 313 older adults (aged 65 +) who completed baseline interviews followed by 4–5 days of ecological momentary assessments approximately every three hours. Individuals reported having no social contact (i.e., solitude) on 11% of the occasions. Solitude predicted lower negative and positive affect on those occasions. The solitude-negative affect link varied by social network quality. Solitude predicted lower negative affect among individuals with more conflictual social networks but not among those with less conflictual networks. Solitude may serve as an adaptive strategy for individuals embedded in demanding or irritating social contexts.